Local Energy Community as a Small Hydrogen Valley H2LEC (London Journal of Engineering Research, 2024)
Local energy community (LEC) is a vertically nested system in energy supply and an ecosystem with joint values and objectives. On-site integrated hydrogen-based systems connected to the grid, consisting of electrolyzer, hydrogen storage and fuel cell system - hydrogen prosumers - provide efficient balancing of local energy consumption and local production of renewable energy that can be extended over annual cycles. There is no transport of hydrogen needed. Thus, H2LEC Local energy community with integrated hydrogen systems - represents the carrier of dispersed energy and hydrogen production as a complement of concentrated energy and hydrogen production: on average, H2LEC will predictably achieve at least 75% self-supply. Additionally, with Combined Heat-and-Power systems, coupling to thermal system adds to energy efficiency.H2LEC represents a virtual socio-economic system based on community values and thus engaging initiative, innovation and capital of local actors, new technology start-ups and local industry; and represents opportunity for new disruptive business models. It brings into the energy supply system new players prosumers, who actively trade their flexibilities among themselves and on the external markets, and stimulates new enabling technologies, notably automated close-to-real time trading, boosting end-to-end automated solutions.The H2LEC create the need and the market for smaller integrated hydrogen-based systems ranging from a few kWe for residential homes to a few MWe units for larger industrial companies or local districts, with complete range of capacities in between, needed for public or tertiary buildings and smaller enterprises. Thus, they provide an opening for participation of SMEs in local and international value chains and will create a strong complementary energy bottom-up pillar and hydrogen supply system locally and in Europe.
Keywords: Adaptive Beamforming; Beam Steering; Location Estimation; Smart Antenna Systems